Misallocation and manufacturing TFP in the market liberalization period of Bolivia - Carlos Gustavo Machicado; Juan Cristóbal Birbuet (Institute for Advanced Development Studies (INESAD), 2009)
This paper analyzes productivity levels, dispersion and growth in the Bolivian Manufacturing Sector during the Market Liberalization Period: 1988-2001. These years are characterized first, by a period of macroeconomic stabilization and 1st Generation Reforms (1988-1993), second, by a period of privatization and 2nd Generation Reforms (1994-1997) and third, by a Post-reforms period (1998-2001). The 1st and 2nd Generation Reforms were framed in line with the Washington Consensus and their main objectives were to guarantee macroeconomic stability, to improve the efficiency and allocation of resources in the economy and to promote economic growth with fairness. We show that in contrast to what was expected, productivity in the manufacturing sector decreased steadily. We compute Total Factor Productivity (TFP), for the first time, using firm-level data and in addition we break down this measure in productivity per se and resource misallocation. We find that both issues contributed to the decline in productivity and if resource misallocation were eliminated, the gains in productivity would have been in the order of 60 percent, but the trend of productivity along time would have been the same, which means that there are also structural problems that affect productivity in Bolivia. In addition, we evaluate TFP considering exporting firms, size of firms, age of firms and geographical location.
Keywords: D24; L1; L6; 330; TFP; Market Structure; Manufacturing